The Designing of CAHWANI Based on IoT as an Alternative Media for Mathematics Learning With Islamic Character In Inclusive Schools - Lailatul Mukarromah; Dwi Apriyanto; Yuni Verawati (Universitas Islam Jember, 2020)
Inclusive schools are educational institutions that include all children and children with special needs (ABK) in the same learning process. According to the study of literature, inclusive schools require learning media with more concrete images and real objects, especially in the field of mathematics. The purpose of this research is to design CAH WANI as a medium of mathematics learning that can improve mathematics learning achievement in inclusive schools. This media is made based on IoT with the aim to facilitate teachers in monitoring children's learning outside of school and determine the appropriate actions to be taken in the next learning process in order to give birth to students who are superior and of Islamic character. In addition, with this media parents are also facilitated in monitoring the learning process of children at school. The research method used is the research and development method, with the chosen development design using the ADDIE development model. This learning media is designed with the original Indonesian puppet concept with a size that is easy to carry and is equipped with a camera that is controlled by a microcontroller and connected to the internet. Product development validation includes (1) subject matter expert test, (2) instructional media expert test, and (3) design design expert test. The results of this study are in the form of an IT-based Islamic learning media design of Islamic character